2007
DOI: 10.1287/mnsc.1060.0640
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Motivation Dynamics and Incentives

Abstract: F irms can increase profitability by appropriately motivating managers. We investigate drivers of managerial motivation, and propose how firms can use performance pay to alter motivational patterns. We focus on the agent's optimal effort decision in trading off compensation utility with effort cost in a static and dynamic setting. Surprisingly, we find that lower risk aversion or increased pay are not necessarily motivating factors, and identify the relevant effort drivers underlying the agent's utility and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In emerging markets it is especially important for a company to keep up the staff's motivation and maintain a positive set of attitudes (Du & Choi, 2010). Even though money is not necessarily qualified as a motivational factor (Kocabiyikoglu & Popescu, 2007), it can help to show the company's appreciation of the employee accepting the job and the employee's willingness to take personal risk for the company's sake. Employees perceiving their efforts being rewarded are more likely to develop positive attitudes (Chênevert & Tremblay, 2009).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…In emerging markets it is especially important for a company to keep up the staff's motivation and maintain a positive set of attitudes (Du & Choi, 2010). Even though money is not necessarily qualified as a motivational factor (Kocabiyikoglu & Popescu, 2007), it can help to show the company's appreciation of the employee accepting the job and the employee's willingness to take personal risk for the company's sake. Employees perceiving their efforts being rewarded are more likely to develop positive attitudes (Chênevert & Tremblay, 2009).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…We can link this to the research of Nientied & Toska (2019), who found that monetary valuation and career opportunities are not the most critical motivational factors and do not have such motivational strength. Conversely, research by Kocabiyikoglu & Popescu (2007) showed that salary is considered a necessary motivating factor. Diskiene et al (2019) also focused on the sub-issue of the influence of managerial decision-making on employee in terms of motivation.…”
Section: Discussionmentioning
confidence: 98%
“…Other factors included potential productivity gains, alomng with genuine interest in the employees and their health. Kocabiyikoglu & Popescu (2007) explored the driving forces of managerial motivation, suggesting how organizations can use performance salary to change motivational patterns. Research has found that increased salary is not necessarily a motivating factor.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A closely related research area is the application of PA models (Holmstrom, ; Shavell, ; Holmstrom and Milgrom, ) in salesperson compensation design (for a comprehensive review of the theoretical results, see Salanié, ). Recently, Kocabıyıkoğlu and Popescu () studied agents' motivation with respect to productivity and past performance, time to evaluation, firm's capabilities, and market factors. These studies, in general, do not focus on CS.…”
Section: Literature Reviewmentioning
confidence: 99%